2020
DOI: 10.1186/s12885-020-07606-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between five types of Tumor Necrosis Factor-α gene polymorphism and hepatocellular carcinoma risk: a meta-analysis

Abstract: Background Research focusing on the relationship between five types of tumor necrosis factor-alpha (TNF-α) SNPs and the risk of hepatocellular carcinoma (HCC) were still controversial. Hereby, we performed a meta-analysis to determine the association between TNF-α promoter SNPs: -1031 T/C, − 863 C/A, − 857 C/T, − 308 G/A, and − 238 G/A with HCC risk. Methods We interrogated articles from journal database: PubMed, Pro-Quest, EBSCO, Science Direct, and Springer to determine the relationship between five types o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…TNF-α is a crucial inflammatory cytokine in the development of liver disease. This cytokine can cause hepatic injury, cirrhosis, and eventually promote hepatocellular carcinoma [ 41 ]. Also, CRP and IL2 are associated with HCC recurrence [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a crucial inflammatory cytokine in the development of liver disease. This cytokine can cause hepatic injury, cirrhosis, and eventually promote hepatocellular carcinoma [ 41 ]. Also, CRP and IL2 are associated with HCC recurrence [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TNF-α-308 polymorphism has been found to be a significant forecaster for the failure of combined antiviral therapy based on specific HCV genotypes (Jeng et al, 2007). However, some studies have shown no association between TNF-α-308 polymorphism and independent of susceptibility to HCV infection (Wungu et al, 2020). Furthermore, there has been no significant TNF-α-308 polymorphism associated HCV clearance or correlation between TNF-α-308 promoter variants and IFN therapy response (Dogra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, functional studies have revealed that the G allele of the SNP variant −764G/C, situated nearby the IFN-γ promoter region, enhances promoter activity by a factor of two to three fold, correlating with both viral clearance and better treatment response in individuals with HCV infection [ 32 ]. In the context of malignancies, TNFα SNP (−863C/A, −857C/T, −308 G/A, and −238 G/A) was strongly associated with a higher risk of hepatocellular carcinoma (HCC) [ 33 ], and the different combinations of SNPs of TNFα (−238G/A or −308G/A) with IL-10 (−592C/A) were highly prevalent among patients with cervical cancer. PBMC (samples from patients with cervical cancer) activated with PHA also indicated that the TNFα (−308A/A) genotype demonstrated increased proliferation rates, elevated IL-4 and TGF-β, and decreased IL-2 levels [ 34 ], and it was postulated that SNPs of cytokine genes act as the potential predictors of cervical HPV infection progression to neoplasia.…”
Section: Introductionmentioning
confidence: 99%